Comparison of astigmatism correction and visual outcomes in mix-and-match implantations of trifocal intraocular lenses with femtosecond laser-assisted arcuate keratotomy and contralateral bifocal Toric intraocular lenses - Shen, Jiying; Hua, Zhixiang; Zhang, Limei; Zhuo, Baoxian; Shen, Wenqian; Chen, Xuanzhu; Guo, Haike; Yang, Jin (Frontiers in Medicine, 2023)
Introduction Astigmatism reduces the postoperative visual performance after non-toric intraocular lenses (IOLs) implantation, and limits the use of refractive IOLs in cataract surgery. The purpose of this study was to compare the efficacy in astigmatism correction and the postoperative visual outcomes between the implantation of a trifocal IOL with femtosecond laser-assisted arcuate keratotomy (FSAK) in one eye and a bifocal toric IOL (TIOL) in the other, in patients with cataract and moderate astigmatism. Methods This prospective observational paired-eye study enrolled patients with cataract and corneal astigmatism (CA) between 0.75 and 2.25 D in both eyes. The patients underwent a mix-and-match treatment comprising trifocal IOL implantation with FSAK and bifocal TIOL implantation. We compared the visual acuity (VA) at all distances, defocus curve, postoperative refractive astigmatism (RfA), CA, high-order aberrations, modulation transfer function (MTF) curve, and Strehl ratio between the two eye groups. Results In total, 41 patients (82 eyes) were enrolled and completed a 6-month follow-up. The 1- and 3-month uncorrected distance VA and 3-month uncorrected near VA were greater in eyes with bifocal TIOLs than with trifocal IOLs and FSAK (p = 0.036, 0.010, and 0.030, respectively), whereas the latter had greater uncorrected intermediate VA at every visit and greater VA in the intermediate range of defocus curve (at −1.50 and − 2.00 D) than the eyes with bifocal TIOLs. The postoperative RA of the eyes with trifocal IOL and FSAK was significantly higher than that of the bifocal TIOL-implanted eyes at the 3- and 6-month follow-ups. Discussion Both FSAK and TIOL implantation effectively reduce pre-existing moderate astigmatism in patients with cataract. The eyes with bifocal TIOLs had more stable long-term astigmatism correction, whereas those with trifocal IOLs and FSAK had better intermediate VA. Therefore, a mix-and-match implantation of trifocal IOL with FSAK and contralateral bifocal TIOL could achieve effective astigmatism correction and provide an overall optimal VA.